The radio JOVE Project 2.0 - Higgins, C.; Fung, S.; Garcia, L.; Thieman, J.; Sky, J.; Typinski, D.; Flagg, R.; Brown, J.; Reyes, F.; Gass, J.; Dodd, L.; Ashcraft, T.; et al. (My University, 2023)
Radio JOVE (radiojove.gsfc.nasa.gov) is a well-known public outreach, education, and citizen science project using radio astronomy and a hands-on radio telescope for science inquiry and education. Radio JOVE 2.0 is a new direction using radio spectrographs to provide a path for radio enthusiasts to grow into citizenscientists capable of operating their own radio observatory and providing science{quality data to an archive. Radio JOVE 2.0 uses more capable software defined radios (SDRs) and spectrograph recording software as a low cost ($350) radio spectrograph that can address more science questions related to heliophysics, planetaryand space weather science, and radio wave propagation. Our goals: (1) Increaseparticipant access and expand an existing radio spectrograph network (2) Test anddevelop radio spectrograph hardware and software (3) Upgrade the science capabil-ity of the data archive (4) Develop training modules to help people become citizenscientists
Planetary, Solar and Heliospheric Radio Emissions IX
PUBLISHED